Incidence and risk factors of acute kidney injury in cancer patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Liu, Caihong; Wei, Wei; Yang, Letian; Li, Jian; Yi, Cheng; Pu, Yajun; Yin, Ting; Na, Feifei; Zhang, Ling; Fu, Ping; Zhao, Yuliang (Frontiers in Immunology, 2023)
Background The incidence and risk factors of acute kidney injury (AKI) in patients with malignancies receiving immune checkpoint inhibitors (ICIs) are being extensively reported with their widespread application. Objective This study aimed to quantify the incidence and identify risk factors of AKI in cancer patients treated with ICIs. Methods We searched the electronic databases of PubMed/Medline, Web of Science, Cochrane and Embase before 1 February 2023 on the incidence and risk factors of AKI in patients receiving ICIs and registered the protocol in PROSPERO (CRD42023391939). A random-effect meta-analysis was performed to quantify the pooled incidence estimate of AKI, identify risk factors with pooled odds ratios (ORs) and 95% confidence intervals (95% CIs) and investigate the median latency period of ICI-AKI in patients treated with ICIs. Assessment of study quality, meta-regression, and sensitivity and publication bias analyses were conducted. Results In total, 27 studies consisting of 24048 participants were included in this systematic review and meta-analysis. The overall pooled incidence of AKI secondary to ICIs was 5.7% (95% CI: 3.7%-8.2%). Significant risk factors were older age (OR: 1.01, 95% CI: 1.00–1.03), preexisting chronic kidney disease (CKD) (OR: 2.90, 95% CI: 1.65–5.11), ipilimumab (OR: 2.66, 95% CI: 1.42–4.98), combination of ICIs (OR: 2.45, 95% CI: 1.40–4.31), extrarenal immune-related adverse events (irAEs) (OR: 2.34, 95% CI: 1.53-3.59), and proton pump inhibitor (PPI) (OR: 2.23, 95% CI: 1.88–2.64), nonsteroidal anti-inflammatory drug (NSAID) (OR: 2.61, 95% CI: 1.90–3.57), fluindione (OR: 6.48, 95% CI: 2.72–15.46), diuretic (OR: 1.78, 95% CI: 1.32–2.40) and angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin-receptor blockers (ARBs) (pooled OR: 1.76, 95% CI: 1.15–2.68) use. Median time from ICIs initiation to AKI was 108.07 days. Sensitivity and publication bias analyses indicated robust results for this study. Conclusion The occurrence of AKI following ICIs was not uncommon, with an incidence of 5.7% and a median time interval of 108.07 days after ICIs initiation. Older age, preexisting chronic kidney disease (CKD), ipilimumab, combined use of ICIs, extrarenal irAEs, and PPI, NSAID, fluindione, diuretics and ACEI/ARB use are risk factors for AKI in patients receiving ICIs. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023391939.